Microcontroller-Based Direct Torque Control Servodrive. (8th February 2020) - Rodríguez-Ponce, Rafael; Mota-Muñoz, Francisco Gustavo
Abstract : Robot technology has become an integral part of the automotive industry in several tasks such as material handling, welding, painting, and part assembly. Therefore, the knowledge and skills to control the electric motors in these manipulators are essential for undergraduate electrical engineering students. Currently, the digital signal processor (DSP) is the core chip in industrial motor-control drives; however, the implementation of DSP control algorithms can be quite challenging for an experienced programmer, even more so for the novice. Considerable research has been done on this topic, although authors usually focus on DSP-based motor drives using popular control techniques such as field-oriented control (FOC). Although highly efficient, this approach is usually reserved for postgraduate education due to its complex structure and functionality. In this paper, the authors present a modular servodrive design on a low-cost, general-purpose microcontroller using the direct torque control (DTC) method, an alternative known for greater simplicity and torque response, compared with FOC. The system design was based on Micropython language allowing the software structure to be more manageable and the code to be more understandable. This design will be useful to undergraduates and researchers with interests in motor control design.